Domestic violence among policemen: rank and spouse employment status as clues (2014)
Interest in domestic violence may have been sustained by concerns about its negative effects on the well-being of victims. Despite 'concerted global effort at reducing domestic violence, gaps still exist in scholarly literature regarding the contributions of personal characteristics to domestic violence. The present study extended domestic violence literature by examining the influence of spouse employment status and rank on domestic violence among personnel of Nigerian Police Force. Participants consisted of 212 purposively selected personnel of the Nigerian Police Force. They included 88 commissioned officers and 144 noncommissioned personnel. Their age ranged from 28 to 57 years. One hundred and forty-three had wives who were employed, while the remainder (69) had non-working wives. After a critical review of domestic violence literature, two hypotheses were tested using t-test of independent samples. Results indicated significant influence of spouse employment status on domestic violence, such that policemen with working spouse were less likely to engage in domestic violence than those with unemployed spouse. However, rank had no influence on domestic violence. Vocational skill acquisition for non-working wives of policemen to enhance their economic contribution to the family is recommended.